Effects of Guanidine Acetic Acid on the Growth and Slaughter Performance, Meat Quality, Antioxidant Capacity, and Cecal Microbiota of Broiler Chickens - Xuedan Li; Zhimin Chen; Jiantao Li (Veterinary Sciences)
The objective of this research was to assess the impact of guanidine acetic acid (GAA) on the growth performance, slaughter outcomes, meat quality, antioxidant capacity, and cecal microbiota of broiler chickens. A total of 128 Arbor Acres broilers were randomly divided into two experimental groups. One group served as the control and was provided with a standard diet, whereas the group treated with GAA received a diet enhanced with 400 mg/kg of GAA. The duration of the experiment was 42 days. Measurements for growth performance, serum biochemical parameters, and antioxidant capacity were conducted both during and at the conclusion of the study, while assessments of slaughter performance and meat quality were carried out solely at the end. Notable differences were observed in terms of growth performance, blood biochemistry, and metabolic parameters between the control and GAA-treated groups (p < 0.05). Hence, these findings imply that dietary GAA supplementation can favorably affect growth, carcass quality, biochemical indicators, and antioxidant capacity in broiler chickens.